2009
DOI: 10.1254/jphs.08275fp
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Suppresses Intercellular Adhesion Molecule-1 Expression via Blocking Nuclear Factor-κB Activation in Human Vascular Endothelial Cells Stimulated by Oxidized Low-Density Lipoprotein

Abstract: Abstract. Atherosclerosis is a complex inflammatory arterial disease. Oxidized low-density lipoprotein (ox-LDL) is directly associated with chronic vascular inflammation. In the current study, we tested the hypothesis that ginkgolide B, a component of traditional Chinese herbal medicine for heart disorder, may affect ox-LDL-induced inflammatory responses in human umbilical vein endothelial cells (HUVECs). The results showed that the ox-LDL treatment caused a significantly increase in the expression of intercel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…Ginkgolide B, the major bioactive component of G. biloba extracts, has been reported to play multiple pharmacological roles as mentioned above (11,14,19,21,38,40). Recent studies have found that ginkgolide B may have anticancer properties in molecular, cellular, and whole animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgolide B, the major bioactive component of G. biloba extracts, has been reported to play multiple pharmacological roles as mentioned above (11,14,19,21,38,40). Recent studies have found that ginkgolide B may have anticancer properties in molecular, cellular, and whole animal models.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the inhibitory effects of casticin on the release of eotaxin, RANTES, VCAM-1, and ICAM-1 in lung epithelial cells and subsequent eotaxin chemotaxis are associated with the suppression of the NF-B signaling pathway. The expression of eotaxin, RANTES, VCAM-1, ICAM-1 and activation of eosinophilic inflammation involved in the pathogenesis of asthma is known to be mediated by the NF-B signaling cascade (Wong et al, 2002(Wong et al, , 2005Kudo et al, 2005;Kletsas et al, 2006;Zerfaoui et al, 2008;Li et al, 2009).…”
Section: Figmentioning
confidence: 99%
“…Oxidized Low-Density Lipoprotein (ox-LDL) plays an important role in the progression of atherosclerosis. 2) Ox-LDL can reduce endothelial regeneration 3) and activate endothelial adhesive properties. In addition, ox-LDL initiates monocyte invasion in subendothelial space.…”
mentioning
confidence: 99%